THE INCREASE IN BLOOD CHOLINESTERASE ACTIVITY FARMERS GROUP EXPOSED ORGANOPHOSPHATE PESTICIDES WERE GIVEN JUICE STRAWBERRIES (FRAGARIA CHILOENSIS) - Anam, Khaerul; Diarti, Maruni Wiwin; Haerani, Irma (Jurusan Analis Kesehatan, Poltekkes Kemenkes Mataram, 2014)
AbstractThe aim of this research is to investigate the activity of the enzyme cholinesterase in the farmer’s blood who had exposed to organophosphate pesticide groups before and after threated with strawberry juice (Fragaria chiloensis). The design of this research is experimental research with pre-post design. Subjects in this research are the farmers who apply pesticides of organophosphate group wich numbered of 32 people. Examination of cholinesterase enzyme activity was performed with Tintometer Color Comparator Cholinesterase kit. The results of this research show a mean activity of the enzyme cholinesterase in the farmer before juice strawberry intake is 71.48% and 82.42% after intake the strawberry juice, this shows an increase of enzyme cholinesterase activity of 10.48%. Conclusion: There is an increase in the enzyme cholinesterase activity after administration of strawberry juice. [JAMBS,2014;1(1):1-15]Keywords: Strawberry Juice, Cholinesterase, Pesticides